2018
DOI: 10.1089/jir.2017.0095
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-34 Aggravates the Severity of Arthritis in Collagen-Induced Arthritis Mice by Inducing Interleukin-17 Production

Abstract: To explore the immunological mechanisms underlying the effect of exogenous interleukin-34 (IL-34) on collagen-induced arthritis (CIA) in mouse. We established a CIA mouse model and injected exogenous recombination mouse IL-34 (rmIL-34) intraperitoneally. The articular index (AI) was measured according to the amount of erythema, swelling, or joint rigidity. The concentrations of TNF-α, IL-17, and IL-6 in CIA mice sera were measured by enzyme-linked immunosorbent assay (ELISA). The mRNA expression levels of TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
See 4 more Smart Citations
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
“…A) . Using the same model, IL‐34 was found to aggravate disease severity by enhancing levels of pro‐inflammatory cytokines such as IL‐6, IL‐17, and TNF‐α …”
Section: Pathological Roles Of Il‐34mentioning
confidence: 95%
See 3 more Smart Citations